1998
DOI: 10.1103/physrevlett.80.4606
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecule Imaging of Fluorescently Labeled Proteins on Metal by Surface Plasmons in Aqueous Solution

Abstract: We report the first real time imaging of single fluorophores attached to protein molecules on metal surfaces in aqueous solution using surface plasmon resonance fluorescence microscopy. The fluorescence was enhanced by the surface plasmons as theoretically predicted for gold and silver. Active movement of single molecules of the fluorescently labeled motor protein, coupled to the ATPase reaction, was observed on the surfaces of gold and aluminum. This microscopy should prove a powerful tool to directly detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 25 publications
1
79
0
1
Order By: Relevance
“…The use of aluminum with fluorescence was not obvious because of earlier reports of strong quenching on aluminum surfaces. 15 However, several reports described the transmission of ultraviolet light by thin aluminum films as seen by excitation of fluorescence with total internal reflection, 16 attenuated total internal reflection, 17 or light scattering. 18 Additionally, aluminum has been suggested for use in SPR, 19 and calculations of the spatial distribution have been reported for fluorophores near an aluminum surface.…”
Section: Resultsmentioning
confidence: 99%
“…The use of aluminum with fluorescence was not obvious because of earlier reports of strong quenching on aluminum surfaces. 15 However, several reports described the transmission of ultraviolet light by thin aluminum films as seen by excitation of fluorescence with total internal reflection, 16 attenuated total internal reflection, 17 or light scattering. 18 Additionally, aluminum has been suggested for use in SPR, 19 and calculations of the spatial distribution have been reported for fluorophores near an aluminum surface.…”
Section: Resultsmentioning
confidence: 99%
“…[4 -8] Molecules adsorbed onto roughened Ag and Au surfaces or nanostructured Ag and Au colloids produce a millionfold increase in the intensity of Raman, [8,9] absorption, [10 -12] and fluorescence emission. [7,13,14] Recently, it has been reported that even single-molecule spectroscopy can be performed by SERS, suggesting that the enhancement factor (EF) can reach as high as 10 14 -10 15 . [15 -19] Second-harmonic generation at the silver-air interface is also enhanced by surface roughness and it is accompanied by a broad luminescence background extending far beyond the anti-Stokes side of the second harmonic.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of SMS method is its ability to observe phenomena hidden in ensemble measurements. 10,[24][25][26][27] A single molecule can be a reporter of its local environment. The reporter properties of the fluorophores can be exploited to reveal inherent differences in local environments or to monitor time-dependent changes in the host.…”
Section: Introductionmentioning
confidence: 99%